If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-5x=+9x
We simplify the equation to the form, which is simple to understand
7-5x=+9x
We move all terms containing x to the left and all other terms to the right.
-5x-9x=-7
We simplify left and right side of the equation.
-14x=-7
We divide both sides of the equation by -14 to get x.
x=0.5
| -2(2-r)=5 | | 2x+2/4=189.5 | | -2(t-3)+8t=3t-4 | | p=17d | | -10-7x=-x-16 | | 2(6x-3)-15=9(x-4) | | (9/4)^2 | | 5m^2+25m-36=0 | | -4/7v=26/3 | | 3=25x+9 | | 9/4^2 | | 4+2/3(2n-9)=14 | | a=w+12 | | 4x^2-9x+22=0 | | -3x+5=-19+3x | | 4(2x-9)+1=8x-35 | | s=-g+70 | | -3x+5y=45 | | (b+7)(b-12)=0 | | 12x^2+15x-18=0 | | 6(-5-7x)=-240 | | 9-3/3+5 | | (4k-3)(4k-3)(3k+1)= | | 5(4d+14)=-130 | | 15y^2+26y+8= | | 12x-8+10x-12= | | 5(4d+14)=-12 | | 6(5-3x)=-168 | | 3X^2-300= | | 9x-18x+45x-90=0 | | -3(-4+6x)=48 | | 2y+5=-1 |